2021
DOI: 10.3389/fneur.2021.685821
|View full text |Cite
|
Sign up to set email alerts
|

Admission and Readmission/Death Patterns in Hospitalized and Non-hospitalized First-Ever-in-a-Lifetime Stroke Patients During the First Year: A Population-Based Incidence Study

Abstract: Background: Hospitalization and readmission rates after a first-ever-in-a-lifetime stroke (FELS) are considered measures of quality of care and, importantly, may give valuable information to better allocate health-related resources. We aimed to investigate the hospitalization pattern and the unplanned readmissions or death of hospitalized (HospS) and non-hospitalized stroke (NHospS) patients 1 year after a FELS, based on a community register.Methods: Data about hospitalization and unplanned readmissions and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Although none of the remaining studies assessed predictors of readmission costs, several of them identified predictors associated with increased readmission rates in stroke survivors and potentially indirectly associated with higher readmission costs. The recognition of these potentially modifiable predictors is important since it may help healthcare organizations better allocate resources and implement targeted readmission reduction policies [ 71 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although none of the remaining studies assessed predictors of readmission costs, several of them identified predictors associated with increased readmission rates in stroke survivors and potentially indirectly associated with higher readmission costs. The recognition of these potentially modifiable predictors is important since it may help healthcare organizations better allocate resources and implement targeted readmission reduction policies [ 71 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…4,5 The influence of recurrent embolism on the functional outcomes of post-stroke patients highlights the significance of investigating prevention strategies and enhancing long-term prognostic methods to stratify patient risk and improve functional outcomes. 6,7 For these reasons, evaluating a patient's early embolisation activity would be beneficial in optimising management and preventing a poorer outcome. Transcranial Doppler (TCD) provides a unique opportunity to detect embolic material in the cerebral circulation at the bedside in a non-invasive manner.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 The influence of recurrent embolism on the functional outcomes of post-stroke patients highlights the significance of investigating prevention strategies and enhancing long-term prognostic methods to stratify patient risk and improve functional outcomes. 6,7…”
Section: Introductionmentioning
confidence: 99%